Soy isoflavone supplementation in healthy men prevents NF-κB activation by TNF-α in blood lymphocytes - Davis, Joanne N; Kucuk, Omer; Djuric, Zora; Sarkar, Fazlul H (Free radical biology & medicine, 2001)
Dietary intake of soy has been associated with a decreased risk of cancer. Soy isoflavones have been postulated to be the protective compounds in soybeans; however, the precise mechanism by which soy isoflavones prevent human cancer is not known. The major soy isoflavones, genistein and daidzein, are antioxidant compounds, therefore one possible mechanism of action is through their antioxidant effect. We have previously demonstrated that the soy isoflavone, genistein, inhibits the activation of the redox-sensitive transcription factor, NF-kappa B, in prostate cancer cells in vitro. In this study, we have demonstrated that genistein, but not daidzein, inhibits TNF-alpha-induced NF-kappa B activation in cultured human lymphocytes. Additionally, we investigated the in vivo effect of soy isoflavone supplementation on NF-kappa B activation induced by TNF-alpha in vitro in peripheral blood lymphocytes of six healthy men. We show that healthy male subjects receiving 50 mg isoflavone mixture (Novasoy) twice daily for 3 weeks are protected from TNF-alpha induced NF-kappa B activation. Additionally, we observed a reduction of 5-hydroxymethyl-2'-deoxyuridine (5-OHmdU), a marker for oxidative DNA damage, following isoflavone supplementation. The inhibitory effect of soy isoflavones was no longer present 3 months after the supplementation. This preliminary study demonstrates that soy isoflavone supplementation may protect cells from oxidative stress-inducing agents by inhibiting NF-kappa B activation and decreasing DNA adduct levels.